Identifying and Characterizing Trans Women in the Swiss HIV Cohort Study as an Epidemiologically Distinct Risk Group. (20th July 2021) - Nguyen, Huyen; Hampel, Benjamin; Garcia Nuñez, David; Battegay, Manuel; Hachfeld, Anna; Bernasconi, Enos; Calmy, Alexandra; Cavassini, Matthias; Vernazza, Pietro; Fellay, Jacques; Rudolph, Hannes; Huber, Michael; et al.
Abstract: Background: As trans women are disproportionately affected by the HIV epidemic, and are still understudied, we aimed to identify and characterize the trans women in the Swiss HIV Cohort Study (SHCS). Methods: A combination of criteria from pre-existing cohort data was used to identify trans women. Information on socioeconomic factors, clinical data, risk behaviors, and mental health was collected. We also described their phylogenetic patterns within HIV transmission networks in relation to other risk groups. Results: We identified 89 trans women of a total 20 925 cohort participants. Trans women were much more likely to be Asian (30.3%) and Hispanic (15.7%) than men who have sex with men (MSM) (2.5% and 4.1%; P < .001) and cis heterosexual (HET) women (7.0% and 3.3%; P < .001). Trans women were more similar to cis HET women in some measures like educational level (postsecondary education attainment: 22.6% and 20.7% [ P = .574] vs 46.5% for MSM [ P < .001]), while being more similar to MSM for measures like prior syphilis diagnosis (36.0% and 44.0% [ P = .170] vs 6.7% for cis HET women [ P < .001]). 11.2% of trans women have been previously hospitalized for psychological reasons compared with 4.2% of MSM ( P = .004) and 5.1% of cis HET women ( P = .025). Analysis of transmission clusters containing trans women suggested greater affinity within the transmission networks to MSM compared with cis HET women. Conclusions: Trans women are epidemiologically distinct in the setting of the Swiss HIV epidemic, warranting better identification and study to better serve this underserved risk group. Abstract : We identified and characterized 89 trans women from the Swiss HIV Cohort Study. In terms of sociological and clinical data, and high-risk behaviors, they are epidemiologically distinct from cis heterosexual women and men who have sex with men, and are found in various transmission contexts.